EVALUASI PELAKSANAAN ASAS GOOD COOPERATIVE GOVERNANCE MELALUI PENGENDALIAN INTERNAL TERHADAP AKTIVITAS SIMPAN PINJAM PADA KOPERASI (KPRI X) DI SIDOARJO - Sheilla Erdini Arfaprimasari; Senny Harindahyani (CALYPTRA, 2018)
Abstract - Implementation of good governance is not only required by private companies or BUMNs, but also required in all organizations such as cooperatives. Good Cooperative Governance (GCG) can assist in achieving organizational goals and determining performance monitoring techniques. The implementation of the five GCG principles is influenced by the role of internal controls, it is necessary to apply appropriate internal controls to enable the cooperative to operate effectively. This study aims to evaluate the application of internal controls in support of the implementation of GCG principles to obtain a picture and knowledge about the effectiveness of internal controls of savings and loan activities that have been applied. The results of research conducted on Cooperative Employees of the Republic of Indonesia (KPRI) X in Sidoarjo showed that the application of control to support the achievement of GCG has been implemented quite effectively because most of KPRI X has implemented GCG principles and internal control has been run in accordance with the objectives.